Floating aging mechanism of lithium-ion capacitors: impedance model and post-mortem analysis - Song, Shuang (2023)
For a new type of energy storage device of lithium-ion capacitor (LIC), it is necessary to evaluate its lifetime for successful market expansion. This paper focuses on explaining the floating aging mechanism under different voltages, combining non-destructive and destructive perspectives. We have accelerated several cells in high temperature climate chambers for overall aging time of more than one year. The floating voltages are set as 2.2, 3 and 3.8 V. The aging mechanism analysis is preliminarily explored using impedance model with both physical meaning and high fitting degree. We perform post-mortem analysis on a brand-new cell and aged ones with different floating voltages to verify the aging mechanism predicted by the impedance model method. We have found that the degradation behavior of high floating voltage is different from that of low floating voltage. The medium voltage region performs well in calendar aging, which is beneficial to the reliability of LIC storage. Some recommendations are given for the non-destructive method, which is helpful for future lifespan research using impedance model.